CURRENT STATUS AND CHALLENGES OF HERBAL DRUG DEVELOPMENT AND REGULATORY ASPECT: A GLOBAL PERSPECTIVE - HOSSAIN, CHOWDHURY MOBASWAR; GERA, MEETA; ALI, KAZI ASRAF (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Conventional herbal medication has picked up a gigantic sum of intrigue around the world due to its viability in the treatment of extreme illnesses from the period of antiquated civilizations. Phytomedicines are considered a major health-care supplier around the globe, especially in rustic and farther ranges. A huge segment of individuals depends on or accept home-grown drugs as an essential cure for different afflictions rather than manufactured drugs. Researchers are paying much attention to herbal medicine as compared to synthetic drugs due to their severe side effects, and toxicity with less efficacy and specificity. Despite the significant increase in global interest in the investigation and development of new botanical products, only a few have been approved till now. Natural product medication development has significant technical and monetary hurdles, including a time-consuming formulation process, quality assurance, safety, therapeutic efficacy, promotion, and administrative issues. To meet these challenges, the regulatory agencies EMEA, ICH, AYUSH, DCGI, WHO, and U.S. FDA trying to bring these herbal drugs under the regulatory pipeline under the NDA approval process. Moreover, the process of drug discovery has also been revolutionized with the new advent of technologies such as the successful drug development of a novel therapeutic agent is critically relying on the process which adopts novel approaches and involves the concept of ADMET (i.e., absorption, distribution, metabolism, excretion, and toxicity) in the early stages of drug discovery along with the interaction profiles of herb-herb and herb-synthetic. In the present review, we will address the noteworthy opportunities and issues related to phyto-drug improvement in various developing and developed nations such as Europe, U.S. and India, its commercialization with regulatory guidelines, and recommended potential methods to bring them up into the mainstream of modern medical practices and healthcare.